2008
DOI: 10.1098/rspb.2008.1157
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific priming of resistance in the red flour beetle, Tribolium castaneum

Abstract: As invertebrates lack the molecular machinery employed by the vertebrate adaptive immune system, it was thought that they consequently lack the ability to produce lasting and specific immunity. However, in recent years, it has been demonstrated that the immune defence of invertebrates is by far more complicated and specific than previously envisioned. Lasting immunity following an initial exposure that proves protection on a secondary exposure has been shown in several species of invertebrates. This phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 228 publications
(245 citation statements)
references
References 44 publications
(82 reference statements)
6
237
1
1
Order By: Relevance
“…We also found that a protective effect of prior treatment with a small dose of the pathogen ('priming') extends for 7 days [previous experiments in this system had only looked for immediate effects and those 2 days following priming exposure (McTaggart et al, 2012)]. This is comparable with the observations of priming after 8 days in beetles (Roth et al, 2009) and 6 days in moths (Tidbury et al, 2011) and shows that priming of the innate system is relatively persistent. This persistent priming also has broad implications for understanding the epidemiological consequences of priming.…”
Section: Research Articlesupporting
confidence: 77%
“…We also found that a protective effect of prior treatment with a small dose of the pathogen ('priming') extends for 7 days [previous experiments in this system had only looked for immediate effects and those 2 days following priming exposure (McTaggart et al, 2012)]. This is comparable with the observations of priming after 8 days in beetles (Roth et al, 2009) and 6 days in moths (Tidbury et al, 2011) and shows that priming of the innate system is relatively persistent. This persistent priming also has broad implications for understanding the epidemiological consequences of priming.…”
Section: Research Articlesupporting
confidence: 77%
“…Importantly, a similar priming of the immune system has now been repeatedly observed in invertebrates that lack the 'adaptive' system, e.g. the crustacean copepod Macrocyclops albicans (Kurtz & Franz 2003), the crustacean water flea D. magna (Little et al 2003), the bumblebee Bombus terrestris (Sadd et al 2005;Sadd & Schmid-Hempel 2006), the beetles Tenebrio molitor (Moret 2006) and Tribolium castaneum (Roth et al 2008) and the fruitfly D. melanogaster (Pham et al 2007). The underlying molecular mechanisms are currently unknown.…”
Section: Immunological Outcomesmentioning
confidence: 99%
“…There have been a number of studies demonstrating that immune priming provides protection to bacteria both within generation (e.g. [14,15]) and transgenerationally (e.g. [11,33,34]).…”
Section: Discussionmentioning
confidence: 99%